RESTRUCTURING, MERGER AND ACQUISITION - Nurhayati; Hasan; Andri Buang; Chairil Anwar; Fetty Herlina; Lukmannulhakim Putra; Indrayani; Muammar Khaddafi (RADJA PUBLIKA, 2023)
Companies need to develop an appropriate strategy in order to maintain its presence and improve its performance. One attempt to become a large company and strong is to implement the strategy of restructuring. The emergence of the free market era has an impact on increasingly fierce corporate business competition. This condition spurred business people to pay attention to the strategy pursued. In fact, the company continues to formulate and perfect its business strategy in order to win the competition. The realignment of restructuring the company`s capital structure can execute through mergers and acquisitions. This research aim is to review the importance of merger activity and investment in terms of objectives and benefits. Methods used a literature review and secondary data. The research suggests that a company merger and acquisition support operation. There is good financial synergy and diversification, achieves economy of scale and scope that leads to cost efficiency and profitability, can obtain management skills, improve market forces, and may also be tax benefits. Because of that, the merger and acquisition were selective to enhance the company`s performance.